Saturation time test of membrane to supply clean water using reverse osmosis with pressure stage in rejection. Issue 1 (January 2021) - Zakwan, Muhammad; Prayoga, Anton; Bismo, Setijo
Abstract: The tsunami in Pandeglang had resulted in high salinity of water and caused water scarcity. Furthermore, there were difficulties accessing water due to dry season in 4 sub-districts in Pandeglang in 2019. Reverse osmosis (RO) is a suitable technology to provide clean water, however, the advanced research is required to undrestand the method and determine the optimum pressure of multi-pass RO to produce clean water with a long saturation time of the membrane. The experimental research used RO multi-pass was operated in Tanjung Lame by various pressures 6-3, 6-4, and 7-4 on the first and second stage to observe the effect of flux decrease and TDS increase throughout 72 hours. Used P1 = 6 bar/P2 = 3 bar showed a better result compared to P1 = 6/P2 = 4 and P1 = 7/P2 = 4 in producing clean water. Provided clean water at 20 ppm has been done by RO multi-pass, which permeates the first stage used as a feed in the second stage. P1 = 6 bar and P2 = 3 bar give the saturation time of membrane 72-80 hour on the first stage and 72-131 hour on the second stage.